Estudo do polimorfismo e desenho de cocristais dos anti-helminticos ricobendazol e albendazol - Silva, Keila Façanha (2016)
The physico-chemical properties of drugs are directly related to their therapeutic efficacy, and these, in turn, are linked to the structural arrangement presented by the drug, which comes from the different conformations and/or intra and intermolecular interactions that define the crystalline packing of molecules in the different solid forms. In this way, knowing and controlling these characteristics is of fundamental importance in the pharmaceutical area. In this context, the present work applied different strategies involving crystal engineering, aiming at the improvement of the biopharmaceutical properties of the drugs: ricobendazole and albendazole. In the case of ricobendazole, crystals were obtained from the slow evaporation technique and, making use of single crystal x-ray diffraction, the crystalline structure of the drug has been clarified, as well as a careful characterization in the solid state was performed. Ricobendazole crystallizes in a monoclinic system belonging to P21/c space group. The crystalline structure is composed of four molecules per unit cell (Z = 4), accommodating a molecule in the asymmetric unit (Z = 1), and possessing the following lattice parameters: a = 7.5960 (16) Å, b = 9.3047 (18) Å, c = 18,726 (4) Å, and β = 82.198 (5)°. For albendazole the objective was to investigate the polymorphic forms reported in the literature, as well as seek new crystalline phases of the drug. There are reported two polymorphic forms, forms I and II, which are enantiotropically related. However, we found that there are three crystalline forms for albendazole, where form I refers to the commercially distributed form, which, when recrystallized in methanol yields a third polymorph, form III. Therefore, the characterization of the polymorphic forms of albendazole was performed, making a comparative study between polymorphic crystal structures which allowed us to investigate their thermodynamic stability. Another strategy applied to drugs covered the development of multi-component crystals with several coformers. Thus, we do a search for co-crystals for both drugs through the solvent-assisted milling and slurry techniques, using a variety of coformers. Promising results were obtained with oxalic acid, salicylic acid, 2.6-dihydroxybenzoic acid, 3.5- dihydroxybenzoic acid and 3.5- dinitroxybenzoic acid. In this way, we obtained possible co-crystals for ricobendazole and albendazole, being these unpublished results for these drugs.